Identifying the Critical Variables Between Corporate Sustainability and Business Strategy: Case Study of PT ISM - Anzala Adli Mandrian; Yudo Anggoro (TIJAB (The International Journal of Applied Business), 2025)
Background: The 2015 Paris Agreement emphasized the need for significant measures to reduce greenhouse gas (GHG) emissions to 45% by 2030 and achieve net zero by 2050. By continuously expanding its business to a global scale, PT ISM has a more significant obligation to be sustainable and socially, environmentally, and ethically responsible. Therefore, the company needs to integrate these aspects into its business operations as smoothly as possible to avoid economic loss and gain competitive advantage. Objective: The goal of this research is to understand the relationship between PT ISM’s sustainability and business-related activities. This research also identifies the critical variables that connect these two concepts by using the sustainability balanced scorecard framework as a basis to develop a corporate-level strategy. Method: Content analysis using ATLAS.ti coding software was utilized to systematically review, note, and group the data from the PT ISM sustainability report into categorized concepts in a coding scheme based on the sustainability balanced scorecard framework. Further analysis was done through co-occurrence analysis using ATLAS.ti to find the intensity of the relationships between these categorized concepts. Result: The coding scheme clearly patterns sustainability and business-related concepts such as GHG emissions, biodiversity, community development, financial performance, and operational efficiency. PT ISM also incorporates many of its sustainability-related activities into its internal processes and organizational capacity based on the intensity of co-occurrence probability. Conclusion: A company's sustainability and business-related activities can be linked using a sustainable balanced scorecard framework. The intensity of these relationships can also be reviewed and identified as a basis for developing an integrated corporate-level strategy that incorporates sustainability and business-related elements. Keywords: balanced scorecard; business strategy; co-occurrence analysis; content analysis; sustainability